Intrapleural fibrinolytic therapy (IPFT) in loculated pleural effusions—analysis of predictors for failure of therapy and bleeding: a cohort study. Issue 2 (31st January 2013) - Abu-Daff, Saleh; Maziak, Donna E; Alshehab, Derar; Threader, Jennifer; Ivanovic, Jelena; Deslaurier, Valerie; Villeneuve, Patrick-James; Gilbert, Sebastian; Sundaresan, Sudhir; Shamji, Farid; Lougheed, Colleen; Seely, Jean M; et al.
Abstract : Objectives: To assess risk factors associated with failure and bleeding in intrapleural fibrinolytic therapy (IPFT) for pleural effusions. Design: Retrospective case series. Setting: Two tertiary-care centres in North America. Participants: We identified 237 cases that received IPFT for the treatment of pleural effusions . Data for 227 patients were compiled including demographics, investigations, radiological findings pretherapy and post-therapy and outcomes. Intervention: Fibrinolytic therapy in the form of tissue plasminogen activator (t-PA) or streptokinase. Primary and secondary outcomes: Success of therapy is defined as the presence of both clinical and radiological improvement leading to resolution. Failure was defined as persistence (ie, ineffective treatment) or complications requiring intervention from IPFT. Incidence of bleeding post-IPFT, identifying factors related to failure of therapy and bleeding. Results: IPFT was used in 237 patients with pleural effusions; 163 with empyema/complicated parapneumonic effusions, 32 malignant effusions and 23 with haemothorax. Overall, resolution was achieved in 80% of our cases. Failure occurred in 46 (20%) cases. Multivariate analysis revealed that failure was associated with the presence of pleural thickening (>2 mm) on CT scan (p=0.0031, OR 3, 95% CI 1.46 to 6.57). Bleeding was not associated with any specific variable in our study (antiplatelet medications, p=0.08). Conclusions: Pleural thickening on a CT scan was found to be associated with failure of IPFT.